Analisis Komparatif Economic Duress sebagai Alasan Penghapus Pidana Pencurian dalam KUHP 2023 dan WvS Belanda - Putri Balgis Khoirun Nisa' (Jurnal Hukum Lex Generalis, 2025)
Article 42 of the 2023Criminal Code creates fundamental ambiguity in accommodating economic duress as a reason for expunging criminal penalties. Through a comparative analysis with noodtoestand Article 40 of the Dutch WvS, economic duress is constructed as an excuse at the level of culpability, not justification. The perpetrator loses minimal freedom of will even though awareness of breaking the law remains. Article 54 paragraph (2) of the 2023 Criminal Code concerning judicial pardon has the potential to become a dead article due to the lack of technical guidelines and normative limitations. In contrast to the Dutch rechterlijk pardon which is binding with clear standards, the Indonesian provisions create the risk of disparity in decisions and dependence on the subjectivity of judges.